Ellagic acid protects ovariectomy‐induced bone loss in mice by inhibiting osteoclast differentiation and bone resorption. Issue 9 (5th February 2020) - Lin, Xixi; Yuan, Guixin; Li, Zhaoning; Zhou, Mengyu; Hu, Xianghua; Song, Fangming; Shao, Siyuan; Fu, Fangsheng; Zhao, Jinmin; Xu, Jiake; Liu, Qian; Feng, Haotian
Abstract: Osteoporosis is a devastating disease that features reduced bone quantity and microstructure, which causes fragility fracture and increases mortality, especially in the aged population. Due to the long‐term side‐effects of current drugs for osteoporosis, it is of importance to find other safe and effective medications. Ellagic acid (EA) is a phenolic compound found in nut galls, plant extracts, and fruits, and exhibits antioxidant and antineoplastic effects. Here, we showed that EA attenuated the formation and function of osteoclast dose‐dependently. The underlying mechanism was further discovered by western blot, immunofluorescence assay, and luciferase assay, which elucidated that EA suppressed osteoclastogenesis and bone resorption mainly through attenuating receptor activator of nuclear factor‐κB (NF‐κB) ligand‐induced NF‐κB activation and extracellular signal‐regulated kinase signaling pathways, accompanied by decreased protein expression of nuclear factor of activated T‐cells calcineurin‐dependent 1 and c‐Fos. Moreover, EA inhibits osteoclast marker genes expression including Dc‐stamp, Ctsk, Atp6v0d2, and Acp5 . Intriguingly, we also found that EA treatment could significantly protect ovariectomy‐induced bone loss in vivo. Conclusively, this study suggested that EA might have the therapeutic potentiality for preventing or treating osteoporosis. Abstract : Our study showed that ellagic acid (EA) inhibited osteoclastogenesis and bone resorption through suppressing receptor activator of nuclear factor‐κB (NF‐κB) ligand‐induced NF‐κB and mitogen‐activated protein kinase signaling pathways in vitro and protected ovariectomy‐induced bone loss in vivo. EA might be a potential compound to treat osteoclast related bone lytic diseases like osteoporosis.